Antithrombotic Therapy in Transcatheter Aortic Valve Replacement - Valvo, Roberto; Costa, Giuliano; Tamburino, Corrado; Barbanti, Marco (Frontiers in Cardiovascular Medicine, 2019)
Transcatheter aortic valve replacement (TAVR) has recently emerged as an effective alternative to medical treatment or surgical aortic valve replacement in all symptomatic patients with severe aortic stenosis and high or prohibitive risk and in intermediate risk when transfemoral access is feasible. Patients undergoing TAVR are often at high risk for either bleeding or cerebrovascular complications, or both, so adjuvant antithrombotic therapies are commonly used before, during and after the procedure. Today, there is no clear evidence on the best antithrombotic regimen in this context. In this review, we will try to go through the mechanisms involved in bleeding and embolic complications and we will discuss the current points of antithrombotic treatment in patients during and after TAVR, with or without oral anticoagulation (OAC) indication.